YY1 Promotes Endothelial Cell-Dependent Tumor Angiogenesis in Hepatocellular Carcinoma by Transcriptionally Activating VEGFA - Yang, Wendong; Li, Zhongwei; Qin, Rong; Wang, Xiaorui; An, Huihui; Wang, Yule; Zhu, Yan; Liu, Yantao; Cai, Shijiao; Chen, Shuang; Sun, Tao; Meng, Jing; et al. (Frontiers in Oncology, 2019)
Hepatocellular carcinoma (HCC) is a typical hypervascular solid tumor that requires neoangiogenesis for growth. The vascular endothelial growth factor (VEGF) is the most potent proangiogenic factor in neovascularization. The multifunctional Yin-Yang 1 (YY1) is involved in the regulation of tumor malignancy of HCC. However, the relationship between YY1 and endothelial cell-dependent tumor angiogenesis in HCC remains unclear. In this study, we observed that YY1 is positively correlated with microvessel density (MVD) and poor prognosis in HCC tissues. We further found that YY1 promotes the transcriptional activity of VEGFA by binding its promoter in HCC. The secreted VEGFA from HCC cells activates phosphorylation of VEGFR2 to promotes tube formation, cell migration, and invasion of vascular endothelial cells in vitro, and promotes tumor growth and angiogenesis in vivo. Furthermore, upregulation of YY1 enhanced bevacizumab resistance in HCC cells. These results suggest that YY1 plays critical roles in HCC angiogenesis and bevacizumab resistance by inducing VEGFA transcription and that YY1 may represent a potential molecular target for antiangiogenic therapy during HCC progression.